Examining Travel Habits During the Fourth and Fifth Waves Of The COVID-19 Pandemic - Csilla, Rimoczi; Viktor, Jager; Beatrix, Lenkovics (European Scientific Journal, ESJ, 2023)
Due to changes in the structure and system of the consumer society, the previously used consumer, geographical, and demographic characteristics did not prove sufficient for the exploration and analysis of the reasons behind consumer habits and tourism behaviour. The characterisation of traditional consumer behaviour was complemented by psychological and psychographic factors. These factors also include lifestyle and motivation. As part of a quantitative study based on an online survey, regular travelers were surveyed, alongside Hungarian people interested in traveling. This paper focuses on arranging the measured sample of travelers into homogeneous groups based on their tourism motivation, lifestyle, and travel behaviour as it relates to COVID-19 pandemic. It was also important to describe and characterize the resulting groups of travelers based on their well-identifiable characteristics. The study was conducted as a continuation of foundational research. Previous research analysed the impact of the first three waves of the COVID-19 pandemic on travel behaviour. The results of the present research refer to the effects of the fourth and fifth waves